IL LASER: FULCRO DI GRANDI INFRASTRUTTURE DI RICERCA (Istituto Lombardo - Accademia di Scienze e Lettere - Rendiconti di Scienze, 2014)
An important characteristic of the laser sources consists in the ability to generate short and intense radiation pulses. This feature has stimulated the development of large-scale laser infrastructures mainly dedicated to nuclear fusion. This paper presents the realization of a new research infrastructure “Extreme Light Infrastructure” (ELI) which has conceptually different purposes compared to the others. The main feature consists essentially in the production of an extremely high peak power by using pulses of the duration of a few femtoseconds and of high energy. Focusing these pulses over an area of the size of the laser wavelength one can achieve extremely high intensities, which will enable new research in particle physics, gravitational physics, nonlinear field theory, physics of high pressures, astrophysics and cosmology.